Evaluasi Program ‘Yuk Nabung Saham oleh PT. Bursa Efek Indonesia Terhadap Peningkatan Literasi dan Inklusi Keuangan di Kota Jambi - Sugeng Haryono; Deka Veronica (Universitas Batanghari, 2020)
The growth of investors in the Indonesian capital market as one of the alternatives to public investment is considered quite good Indonesia Stock Exchange (IDX) as the manager of securities sales in Indonesia continues to make efforts to improve the understanding of public investment in the capital market. One of them is by increasing the number of Bank Administrator Of Customer's Fund Account (BANK RDN) and at this time IDX is eager to make the introduction of the program